Desain Pembelajaran Matematika Topik Transformasi Geometri dengan Pendekatan Realistic Mathematics Education Berbasis Etnomatematika - Faiza Izzati Mufti; Tian Abdul Aziz (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The purpose of writing this article is to present a learning design using the Ethnomathematics-based Realistic Mathematics Education learning model to provide several learning design options that can be used by junior high school teachers in providing learning material on geometric transformations. This learning design is devoted to material on geometric transformations, reflection, rotation, dilation and translation which relate to regional culture. This learning design uses steps based on the characteristics of RME. As well as using needs analysis, student analysis, and task analysis.